Perancangan Gedung Serbaguna Di Pondok Pesantren Miftahul Ulum Kabupaten Kubu Raya Kalimantan Barat - Muhammad Subhansyah Ikram; Putra Akbar, Estar; Destria, Caesar (Jurnal Pengabdian UntukMu NegeRI, 2023)
The Community Service Program (PPM) entitled Designing a Multipurpose Building at the Miftahul Ulum Islamic Boarding School, Kubu Raya, West Kalimantan, was motivated by the need for the Miftahul Ulum Islamic Boarding School to fulfill the educational facilities and infrastructure in the form of a Multipurpose Building. The scope of implementation of activities is the planning and design of the Multipurpose Building so that activities can be properly accommodated according to the required capacity and comfort, as well as meeting building technical standards. The method used consists of four stages. First, collecting site data, user requirements and required building technical standards. Second, do space planning and programming analysis. Third, formulate the design concept. Fourth, developing the design into a technical drawing / DED and budget plan. The community or audience in this PPM are the administrators and teaching staff in Miftahul Ulum. The PPM implementing team and the community jointly formulate the space requirements to be met for the multipurpose building, starting from the function of the space, activities in the room, space capacity and space supports. The objective and final result expected from this PPM is the drafting of the Miftahul Ulum Islamic Boarding School's Multipurpose Building Design Document.